Application of salmonella phage to reduce in-vitro and in-vivo colonization of salmonella enteritidis and salmonella typhi - Muayad Ahmed Mahmud; Sherko M. Abdul-Rahman; Aziz M. Jafaar; Zuber I. Hassan (Zanco Journal of Medical Sciences)
Background and objective: Salmonella typhi is the causative agent of enteric fever while Salmonella enteritidis causes gastroenteritis. Lytic bacteriophages can be applied as biocontrol agents to prevent Salmonella infections. The purpose of this study was to prepare a proper Salmonella phage therapy candidate to be used against pathogenic Salmonella enteritidis and Salmonella typhi.